DIVERSIFIKASI DAN TEKNOLOGI PENGAWETAN ALAMI TERHADAP PRODUK OLAHAN IKAN LELE DI DESA SRIKATON, KEC. PONDOK KELAPA KAB. BENGKULU TENGAH - Ratnawati, Devi (Universitas Bengkulu, 2025)
The purpose of this community service activity is to increase knowledge of catfish farmers in Srikaton Village, North Bengkulu, about the need to process catfish into various products that have higher economic value. Community service activities are divided into two stages: counseling and demonstration. In the counseling activity, participants are given provisions on various processing of catfish products and their natural preservation. Then, a demonstration and practice are carried out to directly show how to process catfish into various home industries with economic value. Catfish farmers, PKK mothers, and residents in the surrounding area attended this activity. The result of this activity is that mothers around Srikaton Village can make their own various processed catfish foods in the form of shredded catfish, crackers, and catfish nuggets. The obstacles still faced are self-awareness to become entrepreneurs, and marketing of home industry products that have been produced. This problem can be resolved according to the desired target through systematic and continuous assistance. Keywords: Catfish; catfish floss; catfish chips; catfish nuggets; home industry